The Relationship Of Toxic Workplace Environment, Job Stress, Employee Life Satisfaction And Productivity With Gender And Tenure As Moderating - Nike Larasati; Wisnu Prajogo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Employees often experience unpleasant working conditions in the workplace which is known as the Toxic workplace environment. A toxic workplace environment can be in the form of harassment, bullying, incivility, ostracism, stalking, and abusive supervision. This study examines the effects of a toxic workplace environment on job stress, employee life satisfaction, and employee productivity by adding gender and years of service as moderating variables. This study uses a sample of employees who have worked at least one year of service. Methods of data collection by distributing questionnaires. The data used were 239 of the 245 questionnaires obtained. The results of this study, the first is that the toxic workplace environment has an effect on productivity and job stress, but has no effect on employee life satisfaction. Second, job stress has no effect on productivity but has an effect on employee life satisfaction, and employee life satisfaction has an effect on productivity. Third, gender and tenure do not moderate the relationship between a toxic workplace environment, job stress, employee life satisfaction, and productivity. Keywords: Toxic workplace environment, job stress, employee life satisfaction, productivity, gender, tenure.